Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.4 Exercises - Page 137: 87



Work Step by Step

$f(x)=(x-6)^{-1}$ $f'(x)=(1)(-1)(x-6)^{-1-1}=-\dfrac{1}{(x-6)^2}=-(x-6)^{-2}.$ $f''(x)=(-1)(-2)(x-6)^{-2-1}=\dfrac{2}{(x-6)^3}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.